A paired comparison of tuberculin skin test results in health care workers using 5 TU and 10 TU tuberculin. Issue 8 (1st August 2000) - Stuart, Rhonda L; Bennett, Noleen; Forbes, Andrew; Grayson, M Lindsay
Abstract : BACKGROUND: Historically, 10 TU has been employed in Australia and the United Kingdom to perform the tuberculin skin test (TST). However, this makes it difficult to compare the rates of TST positivity with other countries such as the USA who use 5 TU. To assess the impact of the dose of tuberculin on the TST a comparison was made of TST responses in health care workers given a TST with both 5 and 10 TU. METHODS: Two TSTs were performed simultaneously in each health care worker using 5 and 10 TU. Each dose was randomly assigned in a blinded manner to the right or left forearm and read at 48–72 hours by a single nurse who was blinded to the assignment of the 5 and 10 TU doses. RESULTS: A total of 128 health care workers were enrolled, 119 (93%) of whom had a past history of BCG vaccination. The overall mean difference in paired reaction sizes for the two doses was 1.5 mm with 95% limits of agreement of –3.6 to 6.5 mm. CONCLUSION: A slightly larger TST reading was seen with 10 TU than with 5 TU. The mean difference of 1.5 mm between the two doses should be considered when comparing rates of TST positivity between countries who use different doses of tuberculin to perform the tuberculin skin test.